2007
DOI: 10.1016/j.ijgo.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of misoprostol and manual vacuum aspiration for the treatment of incomplete abortion

Abstract: Although oral misoprostol was less effective than MVA in this study, it was more acceptable to women. Misoprostol is well-suited for use in low-resource settings, and should be promoted as an option for the treatment of incomplete abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 21 publications
11
70
0
8
Order By: Relevance
“…Studies show that women prefer it to invasive surgery, and show that women with incomplete abortions choose medical treatment with misoprostol over surgery for that reason. [8][9][10] For these reasons, this method is slowly gaining attention as an easy to use, feasible, low-cost means of uterine evacuation that could revolutionize treatment for this condition.…”
Section: Treatment Of Incomplete Abortionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies show that women prefer it to invasive surgery, and show that women with incomplete abortions choose medical treatment with misoprostol over surgery for that reason. [8][9][10] For these reasons, this method is slowly gaining attention as an easy to use, feasible, low-cost means of uterine evacuation that could revolutionize treatment for this condition.…”
Section: Treatment Of Incomplete Abortionmentioning
confidence: 99%
“…This dose has successfully evacuated the uterus in over 1000 women in over a half a dozen trials worldwide. 9,10,19,20,11 Recently completed trials testing 400 mcg sublingual misoprostol compared to 600 mcg oral misoprostol found that that the 400 micrograms sublingual dose is as effective as 600 micrograms oral misoprostol when used for treatment of incomplete abortion. 22 Although the data in support of the 400 microgram sublingual misoprostol dose are less extensive, it may be shown in the future to be the optimal dose and route of administration for this indication.…”
Section: Dosage Regimen 11 17 18mentioning
confidence: 99%
See 3 more Smart Citations